2021
DOI: 10.1055/a-1668-9910
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Bis(indolyl)methanes through an Alkylation Reaction of Indoles with Sodium Alkoxides

Abstract: Herein we wish to describe an alkylation reaction of indoles with sodium alkoxides for the synthesis of bis(indolyl)methanes. 1-Tetralone was proved to be an efficient hydrogen acceptor thus avoiding the use of precious transition metals such as Ru and Ir. This reaction features transition metal-free conditions, readily available starting materials, and gram-scale synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 55 publications
(18 reference statements)
0
1
0
Order By: Relevance
“… 25 In 2022, Zhou et al demonstrated a metal-free synthesis of BIMs by the alkylation of indoles with sodium alkoxides. 26 Notably, 1-tetralone (1 equiv.) must be used as the hydrogen acceptor for the facilitation of this reaction.…”
Section: Introductionmentioning
confidence: 99%
“… 25 In 2022, Zhou et al demonstrated a metal-free synthesis of BIMs by the alkylation of indoles with sodium alkoxides. 26 Notably, 1-tetralone (1 equiv.) must be used as the hydrogen acceptor for the facilitation of this reaction.…”
Section: Introductionmentioning
confidence: 99%